Violent conflict and the child quantity-quality tradeoff - Apsara Karki Nepal; Martin Halla; Steven Stillman (Johannes Kepler University of Linz, Department of Economics, 2018)
We show that the exposure to war-related violence increases the quantity of children temporarily, with permanent negative consequences for the quality of the current and previous cohorts. Our empirical evidence is based on Nepal, which experienced a ten year long civil conflict of varying intensity. We exploit that villages affected by the conflict had the same trend in fertility as non-affected villages prior to the onset of conflict and employ a difference-in-differences estimator. We find that women in affected villages increased their actual and desired fertility during the conflict by 22 percent, while child height-for-age declined by 11 to 13 percent. Supporting evidence suggests that the temporary fertility increase was the main pathway leading to reduced child height, as opposed to direct impacts of the conflict.
Keywords: D74; H56; J13; O10; O12; 330; Conflict; violence; quantity-quality model of fertility; height-for-age; Nepal